aIn vitro Cytotoxic and Apoptosis Effects of Vatica diospyroides Symington Type SS Fruit Extracts on Cervical Cancer Cells - Atchara Chothiphirat (2019)
Thesis (M.Sc., Biomedical Sciences)--Prince of Songkla University, 2018